Advanced Technique of Unilateral Biportal Endoscopy on Revision Surgery for Recurred Herniated Interverbral Disc: A Technical Note - Hun-Chul Kim; Jin Young Lee; Hyeon Guk Cho; Jeong Woo Park; Sang-Ho Han; Young-Il Ko (Case Reports in Orthopedics)
Conclusion: Lumbar UBE offers a promising option for safe and effective reoperation in spinal surgery. Our technique, emphasizing bone-centered manipulation and specific strategies for scar tissue management, provides excellent visibility and enables precise tissue handling. Overall, UBE facilitates relatively simple and safe reoperations, contributing to improved patient outcomes in the challenging field of spinal surgery.